ТЕОРЕТИКО-ОРГАНІЗАЦІЙНІ ОСНОВИ ФІНАНСОВОГО РЕГУЛЮВАННЯ ЗЕМЕЛЬНИХ ВІДНОСИН В УКРАЇНІ - Мороз, Василь Васильович (Науковий журнал «Світ фінансів», 2018)
Мороз В. В. Теоретико-організаційні основи фінансового регулювання земельних відносин в Україні. Розглянуто теоретико-організаційні засади фінансового регулювання земельних відносин в Україні. Висвітлено актуальні питання і напрями удосконалення їх фінансового регулювання й оптимального поєднання з ринковим саморегулюванням, а також визначено необхідні умови щодо реалізації цих можливостей. Зроблено висновки щодо підвищення ефективності методів фінансового регулювання земельних відносин, створення фондуземель державноївласності в Україні. Мороз В. В. Теоретико-организационные основы финансового регулирования земельных отношений в Украине.Рассмотрены теоретико-организационные основы финансового регулирования земельных отношений в Украине. Освещены актуальные вопросы и направления совершенствования их финансового регулирования и оптимального сочетания с рыночным саморегулированием, а также определены необходимые условия для реализации этих возможностей. Сделаны выводы по повышению эффективности методов финансового регулирования земельных отношений, создания фонда земель государственной собственности в Украине. Moroz V. Theoretical and organizational basis of financial regulation of land relations in Ukraine. Introduction. In modern conditions the problem of the land relations arrangement in Ukraine is extremely important, because the development of the economy sector depends on its solution. The fact that Ukraine is an agrarian country and one of the most fertile land in the world, actualizes the issue of creating an effective mechanism of land relations, which would stimulate the most effective increase ofthe country budget. In fact, this is the main task of financial regulation in Ukraine.The issues of developing the rent land relations concerning formation of market value of land as an effective factor of economic development, working mutually beneficial rules out of the game between tenants and land owners, establishing the optimal amount of rent, forms of its payment and terms oflease require furtherresearch.Purpose. The purpose of this article is formulation the ways to solve the problem of financial regulation in Ukraine.Results. This research gives a concept of renting. It allows reaching the optimum amount of land use without advancing funds for purchase of land, because expenses will not pay for itself at ratherlow income level soon.Conclusion. This research suggests the following conclusions and recommendations for improving the financial regulation ofland relations in Ukraine:• the role of the state should be decisive in land regulation• it is necessary to carry out activities aimed at creation of effective and adjustable land turnover• financial regulation of property relations should be improved it is necessary to create a fund of state-owned land.